UJI KARAKTERISTIK SPONGE IRON HASIL REDUKSI MENGGUNAKAN BURNER LAS ASITELIN DARI PASIR BESI PANTAI SUWERU JEPARA - Sonar Hariawan; Sugeng Tirta Atmadja; Yusuf Umardhani (JURNAL TEKNIK MESIN, 2015)
Sponge iron is a product in the manufacture of steel that through the process of direct reduction of iron sand. Steel making process flow through the sponge starts from iron sand made pellet or briquettes in the shape of a reduction to sponge with the welding asitelin burner. In this research is made of sponge iron which raw materials iron sand from Suweru beach Jepara. Briquettes are made from a mixture of iron sand 75%, 20% carbon, and 5% tapioca flour as gluten. From taking of sand beach Suweru 5kg, obtained 3,3875 kg of iron sand from extraction process with permanent magnet as much as 2-3 times. After the extraction process, sieving process is carried out using a 100 mesh, obtained 2.2710 kg. So that it can be seen levels of iron sand beach Suweru was 67,75% and 45,42% are raw material that ready for production. Furthermore, the raw material mixing 2,25 kg of iron sand, 0,6% carbon (charcoal) and 0.15 kg of gluten (tapioca flour) with a total weight of 3 kg resulting in ± 70 briquette iron sand through the process of compacting the weight range of 43 grams per briquette. From sampling 3 briquette iron sand is reduced, resulting sponge iron by weight of 13,98 grams, 14,83 grams and 17.97 grams that can be known percentage yield of 36.68% reduction process. Results of testing the composition of the AAS method, the composition of the raw materials obtained 1.63% Mg, 2.63% Si, 7.30% C, and 49.90% Fe. However, after the reduction process, the composition of the sponge iron 1.4% Mg, 1.42% Si, 1.90% C, and 64.12% Fe. From the data shown a significant increase in Fe content of 14.22%, and is accompanied by a decrease in the levels of impurities in the iron sand.